Sex‐specific associations between insulin resistance and bone parameters in overweight and obese older adults. (1st March 2019) - Mesinovic, Jakub; McMillan, Lachlan B.; Shore‐Lorenti, Catherine; Zengin, Ayse; De Courten, Barbora; Ebeling, Peter R.; Scott, David
Summary: Objectives: To determine sex‐specific associations between insulin resistance and bone parameters measured by peripheral quantitative computed tomography in overweight and obese community‐dwelling older adults. Study design: Cross‐sectional study of 79 community‐dwelling overweight and obese adults (mean ± SD age 62.8 ± 7.9 years; body mass index 32.3 ± 6.1 kg/m 2 ; 58% women). Main outcome measures: Peripheral quantitative computed tomography assessed distal radius and tibia trabecular volumetric bone mineral density (vBMD) and proximal radius and tibia cortical vBMD, periosteal circumference, endosteal circumference and stress‐strain index. The Homeostatic Model Assessment of Insulin Resistance (HOMA‐IR) score was calculated from fasting glucose and insulin values. Lean mass was assessed using dual‐energy X‐ray absorptiometry. Total minutes of moderate and vigorous physical activity (MVPA) were calculated using the Active Australia Survey. Results: Men and women in this cohort had no significant differences in fasting glucose and insulin concentrations, HOMA‐IR values and diabetes prevalence (all P  > 0.05). In women, HOMA‐IR was positively correlated with proximal radius periosteal and endosteal circumference ( r  = 0.331; P  = 0.034 and r  = 0.325; P  = 0.038, respectively). These associations became nonsignificant in multivariable regression analyses; however, HOMA‐IR was negatively associated with proximal radius cortical vBMD (B = −4.79; 95% CI −8.66, −0.92) after adjusting for age, lean mass and MVPA. All associations between HOMA‐IR and bone parameters became nonsignificant in a sensitivity analysis excluding individuals with diabetes, or self‐reported use of glucose‐lowering medications. There were no associations between HOMA‐IR and bone parameters in men. Conclusions: Homeostatic Model Assessment of Insulin Resistance was negatively associated with radial cortical vBMD in overweight and obese older women, but not in men. Further studies are needed to clarify sex‐specific associations between insulin resistance and bone health in overweight and obese older adults.